2011
DOI: 10.1080/0067270x.2011.609610
|View full text |Cite
|
Sign up to set email alerts
|

Marine fish exploitation during the Middle and Later Stone Age of South Africa

Abstract: access to the Blombos Cave and Blombosfontein 1 and 6 materials and to Hilary Deacon for access to the Klasies River main site fish remains. Sarah Wurz and Petro Keene were very helpful with regards to access of material curated at the IZIKO South African Museum, for which I am grateful, and it was a pleasure working with both of them.Thanks are due to Paul Cowley from the South African Institute of Aquatic Biodiversity (SAIAB) who very kindly and with considerable effort supplied me with a number of species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 443 publications
0
8
0
Order By: Relevance
“…Over 80% of the Klasies fish are small and the most common taxa come from intertidal and estuarine waters, though pelagic fish are also present (von den Driesch 2004). Van Niekerk (2011) found that pelagic fish were more common that estuarine ones in the earliest Blombos phase. While marine fish can sometimes be beached, and seabirds may carry small fish to their nests, this seems not to have been the case for most of the fish species at Blombos.…”
Section: Oreotragus Oreotragusmentioning
confidence: 97%
See 2 more Smart Citations
“…Over 80% of the Klasies fish are small and the most common taxa come from intertidal and estuarine waters, though pelagic fish are also present (von den Driesch 2004). Van Niekerk (2011) found that pelagic fish were more common that estuarine ones in the earliest Blombos phase. While marine fish can sometimes be beached, and seabirds may carry small fish to their nests, this seems not to have been the case for most of the fish species at Blombos.…”
Section: Oreotragus Oreotragusmentioning
confidence: 97%
“…Large fish are represented and species are relatively restricted; most common fish include the black musselcracker (Cymatoceps nasutus), and also the white sea-catfish (Galeichthys feliceps), which has toxic spines that require cooking to denature the Azania: Archaeological Research in Africa 195 poison (Henshilwood et al 2001b). Van Niekerk (2011) concludes that MSA populations were not compelled to catch fish in order to survive, but that they were aware of the resource and were able to draw on it when desired. At Sibudu a few marine fish were transported for at least 15 km from the coast, but freshwater fish could have been obtained locally from the uThongathi River (Plug 2006).…”
Section: Oreotragus Oreotragusmentioning
confidence: 98%
See 1 more Smart Citation
“…In their review of 21 coastal Middle Stone Age sites dated between c. 130 and 40 ka, Will et al (2016) found that, in addition to consuming mollusks (n = 21 sites), foragers subsisted on marine mammals (n = 8 sites), marine birds (n = 8 sites), and marine fish (n = 5 sites). Between 120 and 55 ka, foragers at Klasies, Blombos Cave, and Die Kelders regularly procured substantial amounts of adult cape fur seal (Will et al, 2016), and although low, fish remains at Klasies and Blombos suggest active marine fishing (van Niekerk, 2011). The discovery of whale barnacle remains at Pinnacle Point indicates that humans have been collecting whale meat since at least 160 ka (Marean et al, 2007).…”
Section: Humans Have Exploited Aquatic Resources Deep Into the Pleist...mentioning
confidence: 99%
“…c Henshilwood et al, 2001a, 2001b, 2002d'Errico et al, 2005;d'Errico and Henshilwood, 2007;Vanhaeren et al, 2013. d Henshilwood et al, 2001bThompson, 2008 Thompson andBadenhorst et al, 2016;Roberts et al, 2016;Henshilwood, 2017. e Nel, 2013;Nel andHenshilwood, 2016 f Henshilwood, 2008a;van Niekerk, 2011;Langejans et al, 2012g Fisher et al, 2010 the lithic material recovered from the M3 CI layers represent an assemblage that is characterized by the production of blanks, blades, and flakes, primarily through extensive in situ core reduction. This on-site lithic tool production supports the hypothesis that people occupying Blombos Cave during the M3 phase used the interior part of the cave intensively.…”
mentioning
confidence: 99%